Model of the Relationship of Religious, Image, Trust, and Satisfaction towards Member Loyalty in BMT in Jambi, Indonesia - Enggrani Fitri, lucky; Ridhwan; Setiawan, Dedy (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to evaluate the influence of Religiosity, Image, Trust, Satisfaction, and Loyalty of Baitul Maal wat Tamwil (BMT) members in Jambi, Indonesia, both with and without mediation by the variables image, trust, and satisfaction. Considering that the development of BMT in Jambi is slower than in other provinces in Sumatra, this research was conducted in Jambi, Indonesia. The research design uses quantitative methods with a survey approach to collect primary data through questionnaires distributed to 100 BMT members in Jambi, Indonesia, using a purposive sampling method for sample selection. Quantitative data was then analyzed using the Structural Equation Model (SEM) with the help of SPSS 22 and SmartPLS software. The research results showed that Religiosity significantly influenced BMT's Image, Trust, and Member Satisfaction in Jambi, Indonesia. The image does not affect member loyalty to BMT, but Trust and Satisfaction significantly influence member loyalty to BMT in Jambi, Indonesia. This research is expected to provide theoretical contributions in the field of Sharia marketing management and consumer behavior at BMT, as well as practical contributions for BMT management and related parties as information for determining marketing strategies for BMT products in Jambi, Indonesia to increase satisfaction and loyalty of BMT members in Jambi, Indonesia